Professional training of specialists for tourism at the vocational schools in the context of regional requirements and needs - Alla Boichuk (Vasyl Stefanyk Precarpathian National University, 2017)
The article is devoted to the problem of professional training of future specialists of thetourism industry in vocational schools in the context of regional requirements and needs forexample, Ivano-Frankivsk region. The comparative analysis of the survey of graduates ofvocational schools and employers in the tourism industry regarding tasks connected withprofessional training is conducted and key factors for improvement with training areidentified. Key words: professional training, vocational schools, tourism industry, competitivespecialist, professional competence, professional activities, regional requirements and needs.